Competência em informação na UFPR TV: a inter-relaçâo entre informação, conhecimento e comunicação - Cavalcante, Luciane de Fátima Beckman [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the scenario of the Information Society, University television ( TVU ) is a mean of mass communication that incorporates principles of social structure changes , from the dissemination of culture, knowledge and education , which can favor the formation of attitudes and opinions , instilling critical thinking in individuals, promoting dialogue between society and the University through the dissemination of knowledge produced by academics . As an organization situated in the communication area , TVU is based on information and knowledge and depends on these factors for its maintenance and survival in this environment characterized by complexity, innovation demand and new forms of management, in particular what refers to access and information use in order to build knowledge and serving the academic community . According to this, the central hypothesis of the thesis has been established that information literacy , while link mainstreaming in decision making permeates the processes and activities and interacts with organizational outcomes . So, the central objective was defined as : to identify and analyze the information competence of organizational subjects of a University television and its inter - relationship with access and intelligent use of information and knowledge in order to contribute for building theoretical basis for those interested in developing actions and practices in this direction, and supported on mass communication. For the operationalization of objectives and verification of central research hypothesis , we opted for a case study of descriptive and exploratory nature in University television , at Federal University of Paraná ( UFPR TV ) , using methods as the following instruments to collect data: exploratory visit to the mentioned television and semi - structured interview . As a benchmark for analyzing the data collected we opted for the content method for analysis Laurence Bardin, more specifically, Categorical...

No cenário da Sociedade da Informação a televisão universitária (TVU) é um meio de comunicação massiva que incorpora princípios de mudança da estrutura social, a partir da difusão de cultura, conhecimento e educação, o que pode propiciar a formação de comportamentos e opiniões, incutindo pensamento crítico nos indivíduos promovendo o diálogo entre a sociedade e a universidade por meio da difusão do conhecimento produzido no âmbito acadêmico. Enquanto uma organização inserida na área de comunicação, a TVU está baseada na informação e no conhecimento e depende desses fatores para a sua manutenção e sobrevivência nesse ambiente caracterizado pela complexidade, por inovações e exigências de novas formas de gestão, em especial no que se refere ao acesso e uso da informação para a construção de conhecimento e veiculação à comunidade acadêmica. Nesse sentido, como hipótese central da tese foi estabelecida que a competência em informação, enquanto elo de transversalidade em processos decisórios, perpassa os processos e atividades e interage com os resultados organizacionais. Assim, delimitou-se enquanto objetivo central: Identificar e analisar a competência em informação dos sujeitos organizacionais de uma emissora de televisão universitária e sua inter-relação com o acesso e uso inteligente da informação e do conhecimento, a fim de contribuir com a construção de base teórica àqueles interessados em desenvolver ações e práticas nessa direção e apoiadas na comunicação massiva. Para a operacionalização dos objetivos e verificação da hipótese central de pesquisa, optou-se por um estudo de caso de cunho descritivo e exploratório na Televisão Universitária da Universidade Federal do Paraná (UFPR TV), utilizando enquanto aportes metodológicos os seguintes instrumentos de coleta de dados: visita exploratória junto à televisão citada e entrevista semi-estruturada. Como...
Keywords: Competência em informação; Televisão; Educação; Universidades e faculdades; Processo decisorio; Comunicação; Information literacy